(2a-3b) x (4a-8b)
(5b+9) x(2b-8)
Answers
Answered by
7
Answer :
1)
Now, (2a - 3b) (4a - 8b)
= 2a (4a - 8b) - 3b (4a - 8b)
= 8a² - 16ab - 12ab + 24b²
= 8a² - 28ab + 24b²
2)
Now, (5b + 9) (2b - 8)
= 5b (2b - 8) + 9 (2b - 8)
= 10b² - 40b + 18b - 72
= 10b² - 22b - 72
#MarkAsBrainliest
Answered by
9
Plz see the attachment....☺️
Be brainly.......☺️
Be brainly.......☺️
Attachments:
![](https://hi-static.z-dn.net/files/d0f/c820f25242f8af41830c2afec723514f.jpg)
Similar questions
Science,
8 months ago
Social Sciences,
8 months ago
Physics,
8 months ago
Math,
1 year ago
Math,
1 year ago